Antimony Doped tin Oxide/Multi-walled Carbon Nanotubes: Highly Near-infrared Blocking Coating used for Heat Conservation Windows. (May 2017) - Xingyu, Xu; yuanhao, Wang; Wangshujun,; Lin, Lu
Abstract: In this work, antimony doped tin oxide (ATO)/multi-walled carbon nanotubes (MWNTs) composite coating was prepared by introducing MWNTs and ATO nanoparticles into waterborne polyurethane matrix. This composite coating can be coated effectively on glass substrates with high near-infrared blocking property, which demonstrated a great potential for practical application in energy-saving windows used on modern buildings. The morphology, optical properties and mechanical hardness of coating film were investigated. Compared with blank glass substrates, the coating film retained high transmittance in the visible region but strong shielding in the near-infrared region. Meanwhile, by introducing MWNTs, the coating film was provided the mechanical hardness of 2H-3H.